Analysis of Training Loads among Swimmers with Disabilities during Specific Preparation Period - Karpiel, Z.; Kozikowska, K.; Sasin, D. (Central European Journal of Sport Sciences and Medicine, 2021)
The research goal was to analyse training loads during specific preparation period among swimmers with disabilities. Double examination of 20 athletes with disabilities of motion and sight organs, at the beginning and at the end of the period was conducted. Garmin Forerunner 735XT device was used as a measuring tool, which registered heartbeat rate during training sessions. Records of the heartbeat rate were sent up to Garmin Connect programme, where percentage share of each energy zone in the whole training volume was calculated. Taking into consideration the achieved results, during specific preparation period, swimmers were training mostly with moderate and high intensity and the biggest training volume was registered in zones EN2, EN3 and SP1. Additionally, between the first and the second measurement, the biggest decrease in training volume took place in EN, whereas the biggest increase in training volume took place in zone SP1 what indicates increase of work in the field of specific endurance.